PENGARUH STRES KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PT. PLN PERSERO UPT BOGOR - Tanjung, Brian; Cay, Sam (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the Effect of Job Stres and Job Satisfaction on Employee Performance at PT. PLN Persero UPT Bogor. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 65 employees. Data analysis techniques used are validity test, reliability test, classical assumption test, normality test, multicollinearity test, heroscedasticity test, autocorrelation test, coefficient of determination test and hypothesis test. The results of the study indicate that there is a Simultaneous influence between Job Stres and Job Satisfaction on Employee Performance as evidenced by the results of the calculation obtained F value > F table or (63.116 > 3.145), this is also strengthened by the ρ value <Sig.0.050 or (0.000 <0.050). Thus, H0 is rejected and H3 is accepted. Partially, Job Stres and Job Satisfaction have a positive and significant influence on Employee Performance based on the results of partial hypothesis testing for the Job Stres variable (X1), which obtained a calculated t value > t table (9.808 > 1.669) and a significance value (0.000 < 0.05). Partial hypothesis testing for the Job Satisfaction variable (X2) obtained a calculated t value (6.979 > 1.669) and a significance value (0.000 < 0.05). The results of the Determination calculation obtained an R Square of 0.671, meaning that the Job Stres (X1) and Job Satisfaction (X2) variables together have a 67.1% contribution to Employee Performance (Y). While the remaining 32.9% is influenced by other factors not examined in this study. These findings indicate that Job Stres and Job Satisfaction are important factors that need to be considered in efforts to improve Employee Performance at PT PLN Persero UPT Bogor.